2002
DOI: 10.1001/archopht.120.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Human Limbal Progenitor Cells Expanded on Intact Amniotic Membrane Ex Vivo

Abstract: Background: The transplantation of human limbal epithelium on amniotic membrane as a substrate is a new treatment for limbal stem cell deficiency. Limbal epithelial stem cells are characterized by a slow cell cycle and the lack of K3 keratin and connexin 43 (Cx43), a gap junction protein. We investigated Cx43 expression, gap junction intercellular communication (GJIC), and proliferative activity of limbal epithelium expanded on amniotic membrane. Methods: Connexin 43 expression and bromodeoxyuridine (BrdU) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 26 publications
4
45
0
12
Order By: Relevance
“…It is generally accepted that outgrowth is slower on intact AM than on epithelium-denuded membrane [8,15]. We speculate that the AM cells directly hinder growth, and impair attachment by forming a barrier between the membrane and the limbal cells.…”
Section: Discussionmentioning
confidence: 72%
“…It is generally accepted that outgrowth is slower on intact AM than on epithelium-denuded membrane [8,15]. We speculate that the AM cells directly hinder growth, and impair attachment by forming a barrier between the membrane and the limbal cells.…”
Section: Discussionmentioning
confidence: 72%
“…15 The promotion of epithelization is implemented by the basement membrane of AM that serves as a substrate for normal migration, differentiation, and adhesion of epithelial cells, and prevents epithelial apoptosis. 16 Moreover, the epithelium of AM stimulates healing of the ocular surface by producing several growth factors, such as epidermal growth factor, keratinocyte growth factor, hepatocyte growth factor, and basic fibroblast growth factor. 17 The anti-inflammatory activity of AM might be explained by the presence of receptor antagonist of inflammation mediators including interleukin-1 and regulation of the production of activin.…”
Section: Discussionmentioning
confidence: 99%
“…There are experimental evidences showing that the AM is a natural substrate ideal for restoring the stromal niche of the limbal epithelial cells and the limbal epithelial cells cultivated on intact AM epithelium retain stem cell characteristics. 8,20,29,30 On the other hand, Koizumi et al reported that the cultivated limbal epithelial cells showed faster outgrowth with better stratification in morphology compared with those with intact amniotic epithelial cells. 31 They concluded that the denuded AM is the best carrier for corneal epithelial sheet preparation.…”
Section: Discussionmentioning
confidence: 99%